(untitled) (Economic and Political Thought, 2016)
The article attempts to present the role of mass media in international communication within the specific situation of the Polish-German borderland immediately after 1989. The analysis is based on press releases in Gazeta Zachodnia – Westzeitung, a joint venture of Wrocław based publishing house Fo-Press and Dieter Breuer Verlag, a German publisher from Wiesbaden, published from April 1990 till August 1995. The periodical, having been a private enterprise, is one of the first independent cross-border media projects after the political system transformation in Poland to fulfil the postulates of international editorial boards, cross-border impact and distribution range, and bilingualism in the content of communication, in this case focused on Polish-German issues. The periodical exemplifies the process of the revival of independent journalism in Poland after 1989. Although, the paper did not survive, its functioning was inextricably linked to the transformational changes in Poland – it played a crucial role in creating general opinions about the Germans in Poland and about the Poles in Germany.